Nanocrystal evolution during ultra-fast heating in an amorphous Fe85B15 alloy. (1st March 2023) - Kim, Wan; Duan, Tianrui; Perepezko, John H.
Abstract: During the crystallization of Fe-based metallic glasses the precipitation of the BCC-Fe nanocrystals smaller than the exchange length (30–40 nm) has been reported as an effective strategy for a reduced coercivity and an increased saturation magnetization. In binary Fe-B alloys it has been shown that nanocrystals well below the exchange length can be obtained by rapid heating above 100 K/s. In order to determine if the fast heating process can yield a further refinement in nanocrystal size, the influence of different heating rates (0.17–5000 K/s) on the crystallization behavior of an amorphous Fe85 B15 alloy was investigated using Flash DSC and TEM. Above a critical heating rate (500 K/s), the number density and diameters of BCC-Fe nanocrystals become saturated due to diffusion-field impingement that enriches the amorphous matrix with B that leads to the precipitation of Fe3 B nanocrystals that deteriorate the magnetic properties. Graphical abstract: Image, graphical abstract